Noise pollution in developing countries: Loopholes and recommendations for Vietnam law - Quang Chinh Nguyen; An Thanh Thi Chu; Bao Gia Truong; Duyen Hong Thuc Nguyen (City and Environment Interactions)
Although noise pollution and control are receiving more attention from the authorities, no significant improvement is attained. Regulations on noise pollution in Vietnam are scattered, only providing general principles without clear guidance on sources, national plans, noise maps, and criminal liability. At the same pace, other developing countries face similar problems with noise pollution and control. This study aims to identify loopholes and recommend solutions for Vietnam with implications for other developing countries. The first part of this paper is a Prisma-oriented review of articles combined with hand search and recommendations by legal experts. The second part involves 15 interviews with academics and legal practitioners, environmental scientists, government officials working in environmental legislation and public health. The third part is a content analysis using software with quantitative elements. As part of the findings, the study uncovers major regulatory issues. It also offers specific recommendations such as education and public awareness enhancement, categorizing sources of noise, propaganda on noise reduction, strengthening sanctions, amending specific chapters, applying technology for detection and reporting, committing to social responsiveness/culture, among other solutions.